Profesyonel çalgı eğitimi alan lisans öğrencilerinin duygusal zeka ve iletişim becerileri düzeyleri arasındaki ilişkinin incelenmesi - Türkoğlu, Duygu (My University, 2019)
Bu araştırma profesyonel çalgı eğitimi alan lisans öğrencilerinin duygusal zekadüzeyleri ve iletişim becerileri düzeyleri arasındaki ilişkinin belirlenmesi ve bufaktörlerin hangi değişkenler üzerinde farklılık gösterdiğini ortaya koymak amacıylayapılmıştır.Bu çalışma, Türkiye'den seçilmiş üniversitelerin 2018 - 2019 eğitim öğretim yılındaeğitim fakülteleri ve güzel sanatlar fakülteleri müzik bölümünde okuyan 1. ve 4. sınıföğrencilerinden oluşan 200 kişilik bir grupla hazırlanmış, tarama yöntemi uygulanmışbir araştırmadır.Araştırmada veri toplamak amacıyla, araştırmacının hazırladığı Kişisel Bilgi Formu,Tatar, Tok ve Saltukoğlu (2011) tarafından Türkçe'ye uyarlanan Schutte DuygusalZeka Ölçeği, Balcı ve Ersanlı (1998) tarafından hazırlanan ve geliştirilen İletişimBecerileri Envanteri kullanılmıştır.Araştırmada elde edilen sonuçlar şu şekildedir : Araştırmanın sonucuna göre; iletişim becerileri düzeyleri puanları ile yaş,cinsiyet, mevcut okudukları sınıf, mezun oldukları lise türü, okuduklarıüniversite, çaldıkları bireysel çalgı, çaldıkları çalgı türünü çalışma sıklığı,konsere gitme sıklığı, anne eğitim durumu, baba eğitim durumu, aile tutumudeğişkenleri arasında istatistiksel olarak anlamlı bir fark bulunamamıştır. Öğrencilerin duygusal zeka düzeyi puanları ile yaş, cinsiyet, mevcut okuduklarısınıf, mezun oldukları lise türü, okudukları üniversite, çaldıkları bireysel çalgı,çaldıkları çalgı türünü çalışma sıklığı, konsere gitme sıklığı, konser deneyimleri,anne eğitim durumu, baba eğitim durumu, aile gelir durumu, aile tutumudeğişkenleri arasında istatistiksel olarak anlamlı bir fark bulunamamıştır. Örneklem grubunun aldıkları duygusal zeka düzeyi puanları ile iletişimbecerileri düzeyi puanları arasındaki ilişkiye bakıldığında istatistiksel olarakanlamlı bir ilişki görülmemiştir. Araştırmaya katılan örneklem grubunun, iletişim becerileri düzeyleri puanları ilekonser deneyimleri değişkeni, ailenin gelir durumu ve kendi iletişim becerilerihakkındaki düşünceleri değişkenleri arasında istatistiksel olarak anlamlı bir farkgörülmüştür. Konser deneyimleri değişkeninde 3 ayda 1 kez - ayda 1 kez ilediğer - ayda 1 kez arasında, ailenin gelir durumu değişkeninde 1000 tl - 3000 tlarası - 500 -1000 tl arası ile 3000 tl üzeri - 500 - 1000 tl arasında, kendi iletişimbecerileri değişkeninde ise kısmen yeterli - tamamen yeterli cevapları arasındaanlamlı bir fark vardır. Araştırmaya katılan örneklem grubunun, duygusal zeka düzeyleri puanları ilekendi iletişim becerileri hakkındaki düşünceleri değişkeni arasında istatistikselolarak anlamlı bir fark görülmüştür. Kısmen yeterli - tamamen yeterli cevaplarıarasında anlamlı bir fark vardır.

This research was conducted amongst undergraduates whom have recieved professionalmusical instrument training, to compare and contrast their levels of emotionalintelligence and levels of communication skills, as well as to determine if these factorsand others play a role in creating a difference.This study was conducted using two hundred, first to final year university students,enrolled in the 2018-2019 academic school year, selected from amongst several Turkishuniversities and schools of fine arts dealing with music.In order to gather data for this research, the “Personal Information Form” created by theresearcher, the “Schutte Emotional İntelligence Scale” prepared by Tatar, Tok, andSaltukoğlu (2011), and “Communication Skills Guide” prepared and developed by Balcıand Ersanlı (1998) were used.The results of the research are as follows: Based on the results of the research: There have not been any meaningfulstatistical differences found in the communication skills levels scores betweenpeople of different ages, gender, which grade they are currently in, the type ofhigh school the graduated from, the university they are currently attending, theindividual instrument they play, the amount of time they consistently practiceplaying an instrument, how often they attend concerts, their mothers’ level ofeducation, their fathers’ level of education, or family dynamics. There have not been any meaningful statistical differences found in theemotional intelligence levels scores between people of different ages, gender,which grade they are currently in, the type of high school the graduated from,the university they are currently attending, the individual instrument they play,the amount of time they consistently practice playing an instrument, how oftenthey attend concerts, their mothers level of education, their fathers level ofeducation, or family dynamics. There have not been any meaningful statistical findings in the relationshipbetween the communications skills levels points and the emotional intelligenceskills points recieved amongst the test group. There have not been anymeaningful statistical differences found in the communication skills levelsscores between people of different ages, gender, which grade they are currentlyin, the type of high school they graduated from, the university they are currentlyattending, the individual instrument they play, the amount of time theyconsistently practice playing an instrument, how often they attend concerts, theirmothers level of education, their fathers level of education, or family dynamics. There has been a statistically meaningful difference found between the subjectstaking part in the research relating to the communication skills levels points andthe concert experience factor, family financial situation, and subjects withthoughts based on their own individual communication skills. With the concertexperience factors being once every three months, once per month, about onceper month, with family financial situations putting the monthly total incomebetween 1,000 TL – 3,000 TL, between 500 TL -1,000 TL and over 3,000 TLper month, there has been meaningful findings between subjects that answeredthat they had partially sufficient – fully sufficient communication skills. With the subject group that participated in the research, there were statisticallymeaningful findings in differences between what the subjects felt theiremotional intelligence points and their own communication skills pointsbetween the answers partially sufficiant – fully sufficient.
Keywords: Communication Skills; Çalgı Eğitimi; Duygusal Zeka; Education; Eğitim; Emotional Intelligence; Instrumental Training; İletişim Becerileri; Lisans Eğitimi; Music; Müzik; Öğrenim ve öğretim; Study and teaching; Undergraduate Study